Social Inclusion in Enhancing Political Participation of Marginalized Communities in Indonesia - Burchanuddin, Andi; Sore, Udin B. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This study explores the role of social inclusion in enhancing the political participation of marginalized communities in Indonesia. Marginalized groups such as ethnic minorities, indigenous religious communities, and individuals with socio-economic disadvantages often face significant barriers to political engagement. These barriers prevent their full participation in political affairs, limit their representation in decision-making processes, and affect their socio-political well-being. A qualitative approach is used in this research, with in-depth interviews and participatory observation to understand these barriers and their impact on political participation. The findings show that respondents' social inclusion scores vary, with some reporting positive experiences and feeling accepted in their communities, while others continue to experience discrimination and marginalization. Political participation scores also show significant variation, with respondents citing both positive and negative experiences. The study identifies structural and economic barriers, power imbalances, and lack of political representation as major obstacles to political participation. To address these barriers, a multifaceted approach integrating social, economic, and political dimensions of inclusion is needed. Recommendations include strengthening social inclusion programs, increasing access to information and education, enhancing political representation through affirmative policies and leadership training, addressing economic barriers through financial and logistical support, and building alliances and coalitions to advocate for inclusive political agendas. By implementing these strategies, it is hoped that social inclusion and political participation of marginalized communities in Indonesia can be improved. These measures will help create a more inclusive and democratic political environment, where all citizens have a fair opportunity to participate and influence decisions that affect their lives. Collaborative efforts between the government, civil society, and local communities are crucial to achieving this goal.